Pimecrolimus vs. tacrolimus for the topical treatment of unresponsive oral erosive lichen planus: a 8 week randomized double‐blind controlled study. (4th March 2013) - Arduino, P.G.; Carbone, M.; Della Ferrera, F.; Elia,, A.; Conrotto, D.; Gambino, A.; Comba, A.; Calogiuri, P.L.; Broccoletti, R.
Abstract Background Oral lichen planus (OLP) is a chronic inflammatory disease, affecting nearly 1–2% of the population; Proposed therapies are usually symptomatic and numerous drugs have been used, but recently, it has been published that there is insufficient evidence to support the effectiveness of any specific treatment as being superior. To the best of our knowledge, direct evaluation of the efficacy of topically applied pimecrolimus and tacrolimus in the treatment of atrophic‐erosive OLP, refractory to topical steroids, is still lacking. Objectives To assess the efficacy and safety of topical calcineurin inhibitors for unresponsive OLP. An 8 week randomized, double‐blind controlled trial, followed by a 6 month follow‐up period. Patients were treated with either pimecrolimus 1% cream or tacrolimus 0.1% ointment, both mixed with an equivalent amount of 4% hydroxyethyl cellulose gel. The medications were to be applied twice daily for 2 months. Each patient was examined at the beginning of therapy, and then every 2 weeks during the treatment and every 3 months of follow‐up. Main outcome measures were: (i) to compare the effectiveness of topically applied pimecrolimus and tacrolimus; (ii) to evaluate which is more cost‐effective; (iii) to determine which drug is faster in reducing signs and symptoms and (iv) which gives the longest remission. Results Thirty patients were involved in the study. Both drugs were effective at inducing clinical improvement, with no statistical difference. Pimecrolimus creams revealed a significantly better stability of the therapeutic effectiveness (P = 0.031). Conclusion Both medications would currently appear to be a treatment of choice for patients with unresponsive atrophic‐erosive OLP. Pimecrolimus seemed to be more effective in providing long‐term resolution of signs and symptoms. Future efforts are however needed to obtain more objective evidence of the benefit of these medications in the treatment of immunologically mediated oral mucosal lesion.